2020
DOI: 10.2196/16848
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation, and Evaluation of a Personalized Machine Learning Algorithm for Clinical Decision Support: Case Study With Shingles Vaccination

Abstract: Background Although clinical decision support (CDS) alerts are effective reminders of best practices, their effectiveness is blunted by clinicians who fail to respond to an overabundance of inappropriate alerts. An electronic health record (EHR)–integrated machine learning (ML) algorithm is a potentially powerful tool to increase the signal-to-noise ratio of CDS alerts and positively impact the clinician’s interaction with these alerts in general. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Likewise, a few prior studies have used machine learning and other analytics to examine alert compliance with the goal of alert suppression and reduction of alert future. For example, Chen et al 40 model compliance with a vaccine reminder alert and implement their model to suppress selected alerts; their study demonstrated promising results. Other prior studies (such as Wong et al 41 ) examine factors related to decision support compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a few prior studies have used machine learning and other analytics to examine alert compliance with the goal of alert suppression and reduction of alert future. For example, Chen et al 40 model compliance with a vaccine reminder alert and implement their model to suppress selected alerts; their study demonstrated promising results. Other prior studies (such as Wong et al 41 ) examine factors related to decision support compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The published literature on alert fatigue in the academic sphere started as early as 2007. We collected a total of 341 published items and finally selected a total of 8 [13,15,[29][30][31][32][33][34] that fit our research criteria based on the scoping review in Figure 2. We then entered these items in Microsoft Word and Excel for deeper analysis.…”
Section: Related Work and Research Focusmentioning
confidence: 99%
“…We then entered these items in Microsoft Word and Excel for deeper analysis. We summarize and sort these literatures according to their different key foci, methods, and benefits in Multimedia Appendix 2 [13,15,[29][30][31][32][33][34].…”
Section: Related Work and Research Focusmentioning
confidence: 99%
“… 5–7 In order to initialize and sustain such tools, healthcare systems must make up-front investments in technological infrastructure and organizational structures to develop, deploy, and manage these technologies. 8 , 9 Yet there has been little description about what configuration options exist or analysis of trade-offs between different strategies. 10 An evaluation of steps taken by early-adopter health systems who have deployed AI-CDS into clinical workflow would help guide other health systems that are developing or accelerating their AI-CDS strategies, facilitate collaboration, and spread adoption of AI-CDS at the clinical bedside.…”
Section: Introductionmentioning
confidence: 99%
“…To develop and deploy AI-CDS tools, healthcare systems have to identify use cases, search for vendor solutions or build homegrown AI-CDS algorithms themselves, and coordinate the technological infrastructure to deliver model results at point of care. 9 , 11–13 Decisions are required at the organizational level concerning project governance, how diverse stakeholders are incorporated into design and implementation, and long-term maintenance and quality control. 12 , 14 Technologically, AI-CDS tools can run in real time or at set time points, use single or multiple EHR data sources for training and inference, and deliver results natively in the EHR or stand-alone applications designed for new workflows.…”
Section: Introductionmentioning
confidence: 99%